A literary portrait of a case of Hodgkin lymphoma by Wilkie Collins?. Issue 2 (22nd December 2010) - Fernandez-Flores, Angel
Abstract : In October 1859, 'The Queen of Hearts' was published by Wilkie Collins. This book is a collection of 10 short stories written by the protagonists (three retired brothers), in order to keep their niece (aka the queen of hearts) entertained, until the arrival of her fiancé-to-be. The second story of the book, titled 'Brother Griffith's story of the family secret, ' narrates the death of a young girl who has a slow-growing deforming tumour on her neck. Even with the few clinical details provided by the literary description, the current report examines the possibility of Hodgkin lymphoma as a diagnosis, concluding that the option is not an unwise one.